2006
DOI: 10.4103/0019-5545.31553
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of low intensity conflict (LIC) operations

Abstract: Background:A burgeoning clinical and empirical literature has provided incontrovertible evidence that combat operations exact a heavy toll in terms of human suffering not only on combatants but also military support personnel. Though the Indian army is engaged in low intensity conflict (LIC) operations for over five decades, the psychological effects of LIC deployment on soldiers have not been adequately studied.Aims:To evaluate the psychological effects of deployment in LIC operations on service personnel.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
13
2
Order By: Relevance
“…The one exception in the studies reviewed here is that Chaudhury et al 27 suggest this threshold is closer to 12 months rather than 6 months. However, given the cultural differences between the populations studied by Chaudhury et al 27 (the Indian military) and those studied by the other studies in this review (UK and US militaries), this finding may not be generalisable to ‘Western’ forces. Those serving in the Indian military as opposed to in the UK or US militaries are sent on deployment within or around their own country; they generally have a high level of support from the local population and, perhaps importantly, are able to keep in contact with their family more easily 27…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The one exception in the studies reviewed here is that Chaudhury et al 27 suggest this threshold is closer to 12 months rather than 6 months. However, given the cultural differences between the populations studied by Chaudhury et al 27 (the Indian military) and those studied by the other studies in this review (UK and US militaries), this finding may not be generalisable to ‘Western’ forces. Those serving in the Indian military as opposed to in the UK or US militaries are sent on deployment within or around their own country; they generally have a high level of support from the local population and, perhaps importantly, are able to keep in contact with their family more easily 27…”
Section: Discussioncontrasting
confidence: 64%
“…The results of the studies reviewed here appear to place this threshold at approximately 6 months, or deploying for more than 12 months within the last 3 years 9 14 22 24. The one exception in the studies reviewed here is that Chaudhury et al 27 suggest this threshold is closer to 12 months rather than 6 months. However, given the cultural differences between the populations studied by Chaudhury et al 27 (the Indian military) and those studied by the other studies in this review (UK and US militaries), this finding may not be generalisable to ‘Western’ forces.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Soldiers have occasionally involved in acts of fragging too, when they seriously injure or kill themselves before killing or injuring one or many of their colleagues or seniors [9]. Various studies have frequently reported high rate of post traumatic stress and mental turmoil in soldiers especially when posted in highly hostile or inhospitable terrains [10,11]. Probably no other occupation carries as much risk as that of defence services, for unexpected exposure to trauma, which may come due to being evidence of killing hostile opponent, or the death of colleague in such acts.…”
Section: Stressmentioning
confidence: 99%